Pengaruh Pemberian Seduhan Rosella Terhadap Penurunan Kadar Asam Urat Wanita Menopause - Yohan Yuanta (Puslitbang Sinergis Asa Professional, 2019)
Gout disease is a commonly affects men in aged 30-40 years old, while this disease occurred in women in aged 55-70. The lack of estrogen level is contributing to increase the incidence of gout disease in menopause woman. Menopausal women have two times higher risk of gout disease due to deficit role of estrogen in the removal of uric acid trough urine system. The decrease of estrogen hormone level affect the function of excretion system (Integument and kidney) and also digestive system. While the function of these systems decreased, the residual compound like purin could not be removed trough urine, feces, and sweat. The production of uric acid in human body were linear to the breakdown process of purin. The more purines broken down, the more uric acid is produced. One of the plants that can reduce the uric acid level is Rosella (Hibiscus sabdariffa). The anthocyanins pigment in the calyx of Rosella flower could produce flavonoid compound. The question research of this study is the administration of steeping rosella could reduce the uric acid level in menopause women. Objective: To determine the effect of rosella steeping on decreasing uric acid levels in menopausal women. Method: Pre-experimental with the design of one group pre-post-test have been done, the analysis is using the Wilcoxon test signed rank test. The analysis of results obtained by t-test Sig. (2-tailed) 0.001 which value <0.05 is significantly different. The Rosella steeping administration could affect the decrease of uric acid levels in menopausal women.